2021
DOI: 10.1039/d1ra04222j
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on the coordination of diglycolamide isomers with Nd(iii): extraction, third phase formation, structure, and computational studies

Abstract: The inhomogeneous interactions of M–Oamide in the LII ligand result in differences between the metal-ion extraction performances of two isomeric ligands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…The symmetric stretching absorption peaks of the ether O bond shift from 1117 cm −1 of pure L II to 1121 cm −1 (La), 1122 cm −1 (Nd) and 1125 cm −1 (Eu), respectively. 36 It indicates that the L II molecule can form tridentate complexes with La( iii ), Nd( iii ), and Eu( iii ) through two carbonyl groups and one ether group. The studies by Kou et al illustrated the structure of the complex between L I and Eu( iii ), 16,37,38 and the results showed that Eu( iii ), in the center of the complex, is surrounded by three L I molecules with tridentate coordination, and the L II complex also has a similar structure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The symmetric stretching absorption peaks of the ether O bond shift from 1117 cm −1 of pure L II to 1121 cm −1 (La), 1122 cm −1 (Nd) and 1125 cm −1 (Eu), respectively. 36 It indicates that the L II molecule can form tridentate complexes with La( iii ), Nd( iii ), and Eu( iii ) through two carbonyl groups and one ether group. The studies by Kou et al illustrated the structure of the complex between L I and Eu( iii ), 16,37,38 and the results showed that Eu( iii ), in the center of the complex, is surrounded by three L I molecules with tridentate coordination, and the L II complex also has a similar structure.…”
Section: Resultsmentioning
confidence: 99%
“…† Both L I and L II are coordinated with lanthanide ions as a tridentate ligand, which is in agreement with the previous studies. 36,39 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These interactions contribute to the synergistic effect of anions and cations of ILs for efficient extraction of Nd(III). 30 Effect of Equilibrium Time and I/A. To investigate the minimum time to reach extraction equilibrium, the effect of [Omim][DOP] on the E of Nd(III) under different contact times was studied.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The interactions between three ILs and Nd­(III) include strong attraction and VDW interaction, while the VDW interaction and strong steric effect exist within the ILs. These interactions contribute to the synergistic effect of anions and cations of ILs for efficient extraction of Nd­(III) …”
Section: Resultsmentioning
confidence: 99%